Evidence for preventing EVRB in cirrhotic patients: A systematic review - Liu, Ye; Wang, Xiaoyan; Gu, Yingjia; Niu, Dan (Biomedical papers, 2025)
Systematic strategies for preventing and treating esophagogastric variceal rebleeding (EVRB) are currently inadequate. This systematic review aimed to update this critical gap by searching contemporary studies from major guideline websites, databases, and professional associations focused on EVRB prevention in cirrhosis patients. Key findings highlight evaluation methods, risk management, preventive measures, health education, and follow-up strategies. Notably, a hepatic venous pressure gradient exceeding 18 mmHg is identified as a reliable predictor of gastroesophageal varices (GOV) rebleeding. Effective management of primary diseases is crucial, with methods including antiviral and anti-fibrotic therapies, alcohol avoidance, vaccination, and careful medication management. The combination of nonselective β-blockers (NSBBs) and endoscopic variceal ligation (EVL) is established as the gold standard for secondary EVRB prevention. For patients experiencing recurrent bleeding despite NSBBs and EVL, transjugular intrahepatic portosystemic shunt (TIPS) therapy is recommended. Surgical options, such as surgical shunt and devascularization, are advised for those unsuitable for endoscopic therapy or TIPS, particularly in Child-Pugh A and B patients unresponsive to treatment. Additionally, traditional Chinese medicine options, such as Fufang Biejia Ruangan Tablets, Fuzheng Huayu Capsules, and Anluo Huaxian Pills, have shown promise in improving hepatic fibrosis and GOV in cirrhotic patients. This review offers a comprehensive overview of current prevention and treatment strategies for EVRB, providing valuable insights for clinicians and healthcare professionals.
Keywords: liver cirrhosis; esophagogastric varices; prevention; rebleeding; evidence-based nursing